Calculations for parameters of a stationary reflex discharge - Kovtun, Yu.V.; Ozerov, A.N.; Skibenko, A.I.; Skibenko, E.I.; Yuferov, V.B. (Вопросы атомной науки и техники, 2015)
A variant of the stationary reflex discharge model based on the global (volume-averaged) model is under consideration. The calculation is carried out on the plasma electron density and temperature as a function of the adsorbed power in the reflex discharge, magnetic field value and initial gas pressure. The density of neutral atoms and cathode material ions coming into the discharge by the cathode sputtering mechanism is determined. Рассмотрен вариант модели стационарного отражательного разряда на основе global (volume-averaged) модели. Проведен расчет зависимости плотности и температуры электронов плазмы от адсорбированной мощности в отражательном разряде, величины магнитного поля и начального давления газа. Определена плотность нейтральных атомов и ионов материала катода, поступающих в разряд за счет механизма катодного распыления. Розглянуто варіант моделі стаціонарного відбивного розряду на основі global (volume-averaged) моделі. Проведено розрахунок залежності густини та температури електронів плазми від адсорбованої потужності у відбивному розряді, величини магнітного поля і початкового тиску газу. Визначена густина нейтральних атомів та іонів матеріалу катода, що поступають у розряд за рахунок механізма катодного розпилення.